Sorong Serah Aji Krame in the Novel Merpati Kembar di Lombok by Nuriadi - Lisa Rosalia; Nuriadi; Aswandikari; Saharudin; Ahmad Sirulhaq (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study aims to analyze how the Sorong Serah Aji Krame tradition is represented in Nuriadi’s novel Merpati Kembar di Lombok and compare it with its actual implementation in South Montong Baan Village. The research findings indicate that in the MKL novel, the author narrates the Sorong Serah Aji Krame ceremony using the term